Comparative analysis of first-generation epidermal growth factor receptor inhibitors combined with chemotherapy versus third-generation epidermal growth factor receptor inhibitors in the treatment of advanced non-small cell lung cancer: a systematic review and meta-analysis - Peng, Siyan; Yu, Zhixin; Zhu, Honglin; Liang, Chuwen; Qiu, Huijuan; Hong, Shaodong; Zhou, Yixin (Frontiers in Pharmacology, 2025)
BackgroundIn advanced non-small cell lung cancer with EGFR mutations, third-generation EGFR TKIs (3rd-G TKIs) are currently the preferred first-line treatment. Previous studies have demonstrated that combining first-generation EGFR TKIs with chemotherapy (1st-G TKIs + chemo) also significantly enhances efficacy compared to 1st-G TKIs alone. This study aims to compare the effectiveness of 1st-G TKIs + chemo against 3rd-G TKIs.MethodsWe conducted an indirect meta-analysis of randomized controlled trials comparing 1st-G TKIs + chemo to 3rd-G TKIs. Randomized controlled trials (RCTs) were searched from the PubMed, Embase and Cochrane Library databases. Outcomes included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and grade ≥3 treatment-related adverse events (TRAEs). Data were analyzed using inverse variance and Mantel-Haenszel methods.ResultsTen RCTs with 3,014 patients met the inclusion criteria. Direct comparisons indicated that 1st-G TKIs + chemo significantly improved PFS (HR 0.54, P < 0.001), OS (HR 0.62, P < 0.001), and ORR (RR 1.21, P < 0.001) compared to 1st-G TKIs alone. Indirect comparisons between 1st-G TKIs + chemo and 3rd-G TKIs revealed no significant differences in PFS (HR 1.17; 95% CI, 0.98 to 1.40; P = 0.075) or OS (HR 0.78; 95% CI, 0.56 to 1.07; P = 0.122). Although 1st-G TKIs + chemo showed a 16% improvement in ORR compared to 3rd-G TKIs (RR 1.16; 95% CI, 1.06 to 1.27; P < 0.001), it was also associated with a notable increase in grade ≥3 TRAEs (RR 2.41; 95% CI, 1.63 to 3.57; P < 0.001).Conclusion1st-G TKIs + chemo demonstrated PFS and OS comparable to 3rd-G TKIs. Moreover, 1st-G TKIs + chemo may be a viable option for patients who prioritize a higher response rate.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023461565 identifer, PROSPERO (CRD42023461565).